Hepatoprotective activity of Sonchus asper against carbon tetrachloride-induced injuries in male rats: a randomized controlled trial - Khan Rahmat A; Khan Muhammad R; Sahreen Sumaira; Shah Naseer (BMC, 2012)
Abstract Background Sonchus asper (SAME) is used as a folk medicine in hepatic disorders. In this study, the hepatoprotective effects of the methanol extract of SAME was evaluated against carbon tetrachloride (CCl4)-induced liver injuries in rats. Methods To evaluate the hepatoprotective effects of SAME, 36 male Sprague-Dawley rats were equally divided into 6 groups. Rats of Group I (control) were given free access to approved feed and water. Rats of Group II were injected intraperitoneally with CCl4 (3 ml/kg) as a 30% solution in olive oil (v/v) twice a week for 4 weeks. Animals of Groups III (100 mg/kg) and IV (200 mg/kg) received SAME, whereas those of Group V were given silymarin via gavage (100 mg/kg) after 48 h of CCl4 treatment. Group VI received SAME (200 mg/kg) twice a week for 4 weeks without CCl4 treatment. Various parameters, such as the serum enzyme levels, serum biochemical marker levels, antioxidant enzyme activities, and liver histopathology were used to estimate the hepatoprotective efficacy of SAME. Results The administration of SAME and silymarin significantly lowered the CCl4-induced serum levels of hepatic marker enzymes (aspartate aminotransferase, alanine aminotransferase, and lactate dehydrogenase), cholesterol, low-density lipoprotein, and triglycerides while elevating high-density lipoprotein levels. The hepatic contents of glutathione and activities of catalase, superoxide dismutase, glutathione peroxidase, glutathione S-transferase, and glutathione reductase were reduced. The levels of thiobarbituric acid-reactive substances that were increased by CCl4 were brought back to control levels by the administration of SAME and silymarin. Liver histopathology showed that SAME reduced the incidence of hepatic lesions induced by CCl4 in rats. Conclusion SAME may protect the liver against CCl4-induced oxidative damage in rats.